2017
DOI: 10.1016/j.ebiom.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Underarm Cosmetic Products in Relation to Risk of Breast Cancer: A Case-Control Study

Abstract: BackgroundPrevious studies on breast cancer (BC), underarm cosmetic products (UCP) and aluminum salts have shown conflicting results. We conducted a 1:1 age-matched case-control study to investigate the risk for BC in relation to self-reported UCP application.MethodsSelf-reported history of UCP use was compared between 209 female BC patients (cases) and 209 healthy controls. Aluminum concentration in breast tissue was measured in 100 cases and 52 controls. Multivariable conditional logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…Breast cancers and cysts are mammary gland conditions where emerging evidence are suggesting that Al may be involved in their causation (Darbre, 2016). Al chlorohydrate in antiperspirant cosmetics and other underarm cosmetic products may be an important source of Al exposure (Pineau et al, 2014;Linhart et al, 2017). In a case control study (Linhart et al, 2017), the use of underarm cosmetic products containing Al was significantly associated with breast cancer incidence and the Al levels in breast tissues were significantly higher in breast cancer cases than controls (5.8 versus 3.8 nmol/g).…”
Section: Mammary Gland or Breast Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancers and cysts are mammary gland conditions where emerging evidence are suggesting that Al may be involved in their causation (Darbre, 2016). Al chlorohydrate in antiperspirant cosmetics and other underarm cosmetic products may be an important source of Al exposure (Pineau et al, 2014;Linhart et al, 2017). In a case control study (Linhart et al, 2017), the use of underarm cosmetic products containing Al was significantly associated with breast cancer incidence and the Al levels in breast tissues were significantly higher in breast cancer cases than controls (5.8 versus 3.8 nmol/g).…”
Section: Mammary Gland or Breast Effectsmentioning
confidence: 99%
“…Al chlorohydrate in antiperspirant cosmetics and other underarm cosmetic products may be an important source of Al exposure (Pineau et al, 2014;Linhart et al, 2017). In a case control study (Linhart et al, 2017), the use of underarm cosmetic products containing Al was significantly associated with breast cancer incidence and the Al levels in breast tissues were significantly higher in breast cancer cases than controls (5.8 versus 3.8 nmol/g). Breast cancer patients had higher levels of Al in breast tissues than in blood serum (Darbre et al, 2013b).…”
Section: Mammary Gland or Breast Effectsmentioning
confidence: 99%
“…Parada et al found positive associations between paraben concentrations in urine (methyl- propyl and ∑parabens) and prevalent breast cancer, and negative, non-significant associations with breast cancer mortality [28]. Out of four case-control studies of antiperspirant use and breast cancer risk, two reported no effect [29, 30] and one found an increased risk of breast cancer by use of underarm cosmetics [31]. The forth study reported an association between earlier age at breast cancer diagnosis and longer duration of deodorant use and underarm shaving [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, current evidence on the relationship between cosmetic/PCP use and risk of cancer is not very conclusive. In this regard, in a case-control study comprised by 209 cases of breast cancer and 209 healthy controls, Linhart and Talasz [62] reported that the greater use of underarm cosmetic products was associated with increased risk of breast cancer. Contrary, a cohort study did not found any association between use of skincare products and risk of cancer of the breast and endometrium [63].…”
Section: Use Of Cosmetics and Pcps And Feminine Diseasesmentioning
confidence: 99%